Obstacles to teaching and learning mathematics scheduled for the intermediate stage from the point of view of teachers and students in Iraq (Texas Journal of Multidisciplinary Studies, 2023)
The study aimed to find out the obstacles to teaching and learning mathematics scheduled for the intermediate stage from the point of view of teachers and students in Iraq . The researcher followed the descriptive approach with the same questionnaire, where he directed two questionnaires, the first addressed to mathematics teachers, the sample of teachers reached (61), while the second questionnaire was directed to students amounted to (390) questionnaire, and conducted for both honesty, stability and statistical analysis of their paragraphs. The results of the research were the existence of obstacles to teaching and learning mathematics for the intermediate stage from the point of view of teachers and students in Iraq.